Students’ perceptions of peer feedback in lower elementary school grades - Sablić, Marija (Revija za elementarno izobraževanje, 2025)
This paper presents the results of a study conducted on seventeen first- to fourthgrade elementary school students, the aim of which was to examine the students’ perceptions and assessments of the importance of peer feedback and the ways in which peer feedback is carried out. This paper emphasizes the need to raise awareness of the basic skills that are necessary for effective peer feedback – the development of critical thinking, evaluation, observation skills, communication skills, the development of empathy, self-confidence, and the development of respect for others.
Keywords: learning process; peer feedback; school; student; šola; teaching; učenec; Učenje in poučevanje; učni proces; vrstniška povratna informacija